STONE RELIEFS-DETAILS OF ARCHITECTURAL DECOR OF THE 14th–19th centuries with ARABIC INSCRIPTIONS AND PLANT ORNAMENT, REVEALED in 2022 in the village. KUBACHI - Mammaev, Misrihan Mamaevic; Nurmagomedov, Abdulgamid Magomedovic (History, Archeology and Ethnography of the Caucasus, 2024)
The article describes the stone reliefs-architectural details of the XIV-XIX centuries. with Arabic inscriptions and floral ornaments, some of which (Nos. 1–4,7,9–10) are in the Kubachi Tower Museum, located in the upper quarter of the old part of the village. Kubachi. Reliefs in the museum, taken from the ruins of old buildings of quarter mosques, residential buildings and the palace-type building "Khwalla Khulbe" (Large Houses), brought from the lower quarter of the village. Two reliefs (Nos. 5–6) with Late Kufic Arabic inscriptions combined with floral ornaments, dated to the 14th century, were recorded in the masonry of the walls that form the doorway on the first floor of the quarter mosque, located on the border of the middle and lower quarters of the old part of Kubacha. This mosque with the local name "Kakyabala Mishit", which collapsed in 2019, was restored in 2020–2022. at the expense of the Agency for the Protection of the Cultural Heritage of Dagestan. The reliefs are inserted into the walls of the mosque for decorative purposes. One of the reliefs (No. 8) with Arabic inscriptions, dated to the 14th century, was found in the masonry of the retaining wall of the road leading from the market square (it is also Godekan) to the building of the Kubachi secondary general education school and to the Khyatsila kyullupe water intake source. The wall, in the masonry of which a relief is inserted for decorative purposes, on the right adjoins the arched bridge, located at the southern end of the market square. On the four reliefs under consideration (Nos. 1.5–6.8) formulas of monotheism (shahada) are presented, on two reliefs (Nos. 8–9) building inscriptions are carved. The inscription on one relief (No. 2) mentions the name of Ali, probably the name of the fourth righteous Caliph, cousin and son-in-law of the Prophet Muhammad. Ali’s name, along with the names of other righteous caliphs (Abu Bekr, Omar, Osman) and the name of the Prophet Muhammad, is also presented on other medieval reliefs-architectural details from the village. Kubachi. Only 10 reliefs have been described.